Authenticity in architectural heritage conservation: discourses, opinions, experiences in Europe, South and East Asia - Weiler, Katharina; Gutschow, Niels (Transcultural research-- Heidelberg studies on Asia and Europe in a global context, 2017)
This volume presents colonial and postcolonial discourses, opinions, and experiences in the field of architectural heritage conservation and the use of site-specific practices based on representative case studies presented by art historians, architects, anthropologists, and conservationists from Germany, Nepal, India, China, and Japan. With more than 180 illustrations and a collection of terminologies in German, English, Sanskrit, Hindi, Nevari and Nepali, classical Chinese and standard Mandarin, and Japanese, these cross-cultural investigations document the processual re-configuration of the notion of authenticity. They also show that approaches to authenticity can be specified with key analytical categories from transcultural studies: appropriation, transformation, and, in some cases, refusal